2021
DOI: 10.3399/bjgpo.2021.0049
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease risk communication in NHS Health Checks: a qualitative video-stimulated recall interview study with practitioners

Abstract: BackgroundNHS Health Check (NHSHC) is a national programme to identify and manage cardiovascular disease (CVD) risk. Practitioners delivering the programme should be competent in discussing CVD risk, but there is evidence of limited understanding of the recommended 10 year/centage CVD risk scores. Lifetime CVD risk calculators might improve understanding and communication of risk.AimTo explore practitioner understanding, perceptions and experiences of CVD risk communication in NHSHCs when using two different C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“… 53 Another new study found that practitioners often demonstrated limited understanding and confidence in explaining the 10-year risk score to patients, whereas confidence in the JBS3 lifetime CVD risk calculator, with its visual information summaries, was higher. 54 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 53 Another new study found that practitioners often demonstrated limited understanding and confidence in explaining the 10-year risk score to patients, whereas confidence in the JBS3 lifetime CVD risk calculator, with its visual information summaries, was higher. 54 …”
Section: Discussionmentioning
confidence: 99%
“…A newly retrieved study reported that overall fidelity of delivery of NHS-HCs in general practice was high, however, important elements of the NHS-HC, including assessments in relation to ethnicity and family history of disease, in addition to the Alcohol Use Disorders Identification Test and dementia risk management, were being regularly omitted 53. Another new study found that practitioners often demonstrated limited understanding and confidence in explaining the 10-year risk score to patients, whereas confidence in the JBS3 lifetime CVD risk calculator, with its visual information summaries, was higher 54…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chapter 6 Results 4: video-stimulated recall interviewspractitioners P arts of this chapter have been reproduced with permission from Gidlow et al 75 This is an Open Access article distributed in accordance with the terms of the Creative Commons Attribution (CC BY 4.0) license, which permits others to distribute, remix, adapt and build upon this work, for commercial use, provided the original work is properly cited. See: https://creativecommons.org/licenses/ by/4.0/.…”
Section: Discussionmentioning
confidence: 99%
“… 16 However, challenges remain in understanding, competencies, and training in CVD risk communication for NHS health checks carried out by healthcare professionals. 17 …”
Section: Introductionmentioning
confidence: 99%